Improving Future Street Education Programs: Insights from CSWDO Employees on Access, Inclusion, and Support in Masbate City’s Past Initiative - Orticio, Katrina (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the discontinued Street Education Program in Masbate City by evaluating the perceptions of City Social Welfare and Development Office (CSWDO) employees in terms of access, inclusion, and educational and psychosocial support provided to marginalized youth. Anchored on Social Inclusion Theory, Ecological Systems Theory, and the Rights-Based Approach to Education, the study employed a quantitative descriptive research design involving thirty (30) CSWDO employees selected through purposive sampling. Data were collected using a validated researcher-made questionnaire and analyzed through frequency, percentage, weighted mean, and ranking. Findings revealed that the program provided very sufficient access and strong teaching support, with high participation reach and consistent facilitator guidance. Inclusivity across socio-economic status, gender, and age groups was rated highly, indicating effective reduction of participation barriers. Educational and psychosocial support were frequently provided, with psychosocial support identified as a major strength; however, learning materials were found to be very insufficient, highlighting a key limitation in program implementation. The study concludes that while the program was effective in promoting access, inclusion, and support, its sustainability and overall impact were constrained by inadequate instructional resources. Recommendations emphasized strengthening resource provision, enhancing educational support, and maintaining inclusive and adaptive program strategies. The study aligns with SDG 4 (Quality Education) and SDG 10 (Reduced Inequalities) by addressing equitable access to education for marginalized youth. It contributes to socio-economic, educational, and institutional sustainability by providing evidence-based insights for improving inclusive and community-based education programs.